Clinical patterns of ocular motor and vestibular impairments in professional athletes after sport-related concussion (SRC) and diagnostic challenges: a narrative review - Papciak, Kinga Zofia; Jabłońska, Urszula Zofia; Radliński, Michał; Gardzielik, Aleksandra; Głaszczka, Michał; Korowaj, Karolina; Dercz, Maciej Piotr; Fitas, Alicja; Palacz, Jakub Paweł; Woźniak, Klaudia (Quality in Sport, 2026)
Background. Sport-related concussions (SRC) are complex injuries often involving ocular motor and vestibular impairments. While standardized acute tools, such as the SCAT6, are essential for initial evaluation, they lack clinical sensitivity after the first 72 hours. Furthermore, subacute subjective clinical screening is heavily limited by elite athletes frequently minimizing or concealing symptoms. Aim. The aim of this narrative review is to summarize the existing literature on the clinical patterns of ocular motor and vestibular impairments in professional athletes following SRC, and to highlight the critical need for an objective, multimodal diagnostic approach. Material and methods. A comprehensive literature review was conducted using PubMed and ScienceDirect,incorporating recent clinical studies, international consensus statements, and literature reviews published between 2014 and 2025. The analysis focused on the limitations of traditional subjective symptom reporting and evaluated the clinical utility of objective technological instruments in assessing ocular motor and vestibular impairments in SRC management. Results. The problem with standard concussion tests is that they rely on athletes telling the truth about their symptoms - which they often don't. Technologies like the vHIT and iVOMS get around this issue completely by providing raw, computer-recorded metrics. Because a player has absolutely no conscious control over these automatic physical responses, these tests are a much more reliable way to detect deficits. Conclusions. The management of SRC in professional athletes requires a transition from subjective evaluations to targeted, objective diagnostics. Adding objective technologies to standard clinical screening provides an accurate, data-driven way to track brain recovery. This solves the issue of subjective symptom reporting and ensures proper recovery.